The Effects of MAPCVD-Diamond Coating on the Phase Stability and Microstructure of Zirconia (Y-TZP) Cutting Tool Inserts - Kauri, Inderjeet; Singh, Ramesh (Universiti Putra Malaysia Press, 2001)
Yttria-tetragonal zirconia ceramics (Y-TZP) ceramics is considered as one of the most promising material for cutting tool applications due to its unique combination of chemical, physical and mechanical properties. Although Y-TZP ceramics is tough and strong, tool bits need to be simultaneously hard, tough and wear resistant. However, high hardness is usually associated with brittleness. Hence, there always has to be a compromise between the desired hardness and the necessary toughness. In the present work, the effect of coating a thin film of diamond on the surface of Y-TZP inserts by employing Microwave Plasma Chemical Vapour Deposition (MAPCVD) technique was studied. The Y-TZP inserts were prepared and sintered to full density at 1400·C prior to MAPCVD process. Selected sintered inserts were surface-ground using a coarse and fine SiC paper while another was polished to 1 I'm finish prior to MAPCVD treatment. It has been found that nucleation of CVD diamond particles only occurred on Y-TZP surface polished to 1 IJITl finish. X-ray diffraction (XRD) analysis performed on other Y-TZP inserts did not revealed any strong peaks corresponding to crystaI line diamond phase and these were confirmed using scanning electron microscopy (SEM). However, chemical reaction between Zr and carbon from the reducing atmosphere in the chamber did occur in all of the treated inserts to form a new phase, ZrC. Although diamond nucleation was not observed in both the pre-ground and CVD treated surfaces, SEM examination of these so treated surfaces revealed fine-grained structure believed to have recrystal lised from the severely damaged ground surface.